Transcriptome and metabolome analyses revealed the main profiles contributing the mild aroma characteristics of Artemisia stolonifera - Cao, Ye; Ren, Yan; Wang, Ye; Li, Hui (Frontiers in Plant Science, 2025)
Artemisia stolonifera, identified as an original source of mugwort leaf during the fourth national medicinal resource investigation in China, remains considerably understudied compared to the well-characterized Artemisia argyi, despite its distinctive mild aroma and potential therapeutic value. The lack of systematic comparative analyses on their active compounds and underlying biosynthetic mechanisms has limited the application and development of A. stolonifera. To address this gap, we conducted integrated metabolomic and transcriptomic analyses of leaves from both species. Using GC-MS for targeted profiling of volatile organic compounds and UPLC-ESI (-Q TRA)-MS/MS for flavonoids and lignin pathway intermediates, we identified 1,728 differentially accumulated metabolites (DAMs). Transcriptome sequencing generated 37.61 Gb of clean data, revealing 18,000 differentially expressed genes (DEGs). Kyoto Encyclopedia of Genes and Genomes analysis demonstrated significant divergence in terpenoid and flavonoid biosynthesis pathways between the two species. A. stolonifera exhibited accumulation sesquiterpenoids, consistent with the concerted upregulation of mevalonate pathway genes (e.g., AACT1-4, HMGR1-3) and sesquiterpene synthases (BAS1, LUP2, CAMS1, XF1). Conversely, A. argyi exhibited enrichment of monoterpenoids and flavonoids, associated with elevated expression of methylerythritol phosphate pathway genes (DXS2, DXR1-5), monoterpenoid biosynthesis genes (SDR2-4, TPS14), and flavonoid biosynthesis genes (e.g., CHS1-2, CHI, F3H1-3). This study elucidates the divergence of genetic and metabolic basis governing bioactive compound biosynthesis between these species, revealing that the characteristically mild aroma of A. stolonifera results from its lower volatile oil content and reduced levels of intense monoterpenoids. These insights provide a critical foundation for evaluating the medicinal value and supporting the safe utilization of A. stolonifera.